PENDAPATAN DAN TINGKAT KESEJAHTERAAN SUBJEKTIF KELUARGA PETANI ALIH KOMODITI PADI KE KARET DI KECAMATAN ABUNG SURAKARTA KABUPATEN LAMPUNG UTARA - Miswati, Ayu Sari; Lestari, Dyah Aring Hepiana; Marlina, Lina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This research aims to analyze the income of rubber plantation in the past year and the subjective welfare level of farmer household who switch commodity from rice plant to rubber in District of Abung Surakarta. This research was conducted in February-March 2019 using a survey method. The number of respondents was 56 farmers using simple random sampling technique. Data are analyzed using descriptive statistical methods and inferencing statistics and the analysis tools used are farm income and subjective welfare indicators using a Likert scale from strongly disagree to strongly agree. The results of the analys showed that the average income of rubber farming based on cash costs and the total costs are Rp27,821,627.65 / hectar / year and Rp18,357,350.60 / hectare / year. Farmer households are dominated by subjective welfare in high level criteria. Key word: farming income, subjective welfare, transfer of commodity